2023
DOI: 10.1249/mss.0000000000003170
|View full text |Cite
|
Sign up to set email alerts
|

Microbiota Mediate Enhanced Exercise Capacity Induced by Exercise Training

Abstract: The gut microbiota is critical to host metabolism and is influenced by many factors, including host genotype, diet, and exercise training.PurposeWe investigated the effects of gut microbes, and the mechanisms mediating the enhanced exercise performance induced by exercise training, i.e., skeletal muscle blood flow, and mitochondrial biogenesis and oxidative function in male mice.MethodsAll mice received a graded exercise test before (PRE) and after exercise training via forced treadmill running at 60% to 70% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
1
0
Order By: Relevance
“…In contrast, physical activity, higher education, higher income, and being married is associated with improved vascular outcomes and decreased risk for hypertension [ 3 , 32 35 ]. Physical activity and habitual exercise may have a favorable effect on the gut microbiome [ 36 , 37 ]. A study by Xia et al found spontaneous hypertensive rats had a significant decrease in systolic blood pressure following a 12-week moderate exercise intervention that correlated with a decreased abundance of several pathogenic microbial strains [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, physical activity, higher education, higher income, and being married is associated with improved vascular outcomes and decreased risk for hypertension [ 3 , 32 35 ]. Physical activity and habitual exercise may have a favorable effect on the gut microbiome [ 36 , 37 ]. A study by Xia et al found spontaneous hypertensive rats had a significant decrease in systolic blood pressure following a 12-week moderate exercise intervention that correlated with a decreased abundance of several pathogenic microbial strains [ 38 , 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed that mice subjected to physical training exhibited significant improvements in performance, such as distance covered and time to exhaustion, alongside increases markers like adenosine monophosphate (AMP)-activated protein kinase (AMPK), sirtuin-1, citrate synthase activity, mitochondrial IV complex, and nitric oxide. However, these effects disappeared when the animals were treated with antibiotics [17 ]. Another experimental study found that the gut microbiota regulates glycogen stores, a factor that also impacts physical performance, reinforcing the role of the gut microbiota as a moderator of adaptations derived from physical exercise [18 & ].…”
Section: Microbiome and Athletic Health And Performancementioning
confidence: 99%